Cutaneous melanoma attributable to UVR exposure in Denmark and Germany. (December 2021) - Keim, Ulrike; Gandini, Sara; Amaral, Teresa; Katalinic, Alexander; Holleczek, Bernd; Flatz, Lukas; Leiter, Ulrike; Whiteman, David; Garbe, Claus
Abstract: Background: Increasing incidence rates of cutaneous melanoma (CM) observed during the last five decades in white populations are largely attributed to increased exposure to solar ultraviolet radiation (UVR), often expressed as population attributable fraction (PAF). Thus, many CMs could be prevented by reducing UVR exposure. The aim of this study was to estimate the PAF of CM attributable to UVR exposure and demographic changes in Denmark and Saarland/Germany for the period 1943 to 2036. Material and methods: CM incidence data (ICD-10, C43) for Denmark (1943–2016) and the German Federal State of Saarland (1972–2016) were retrieved from the NORDCAN database and from the Saarland Cancer Registry. The number of CMs attributable to UVR exposure was calculated by comparing contemporary or predicted CM incidence rates with CM rates in Denmark during the years 1943–1946. Results: In Denmark, the proportion of CM cases attributable to UVR exposure increased from around 20% in 1947–1951 to 96% in 2012–2016; in the Federal State of Saarland, it increased from 50% in 1972–1976 to 90% in 2012–2016. Until 2032–2036, the PAF is expected to rise in Denmark to 97% and in the Saarland to 92%. The demographic influence, on the other hand, is rather small. Conclusions: More than 90% of all CM in Germany and Denmark are attributable to UVR exposure, and in principle, preventable. These findings underline the need for primary prevention strategies, aiming to increase the awareness of melanoma and its risk factors and to promote behavioural changes that decrease sun exposure. Highlights: Long-term estimates of UVR-related CM burden in Denmark and Germany from 1943 to 2036. In 2012–2016, over 90% of CM cases in Denmark and Germany were attributable to UVR. Increasing UVR-related CM burden is to be expected if risk behaviour does not change. Primary prevention focusing on reducing UVR exposure is crucial for CM control.